Advancements in nasal drug delivery system of natural products - Hsu, Yenna; Yang, Jiajing; Cao, Miaoyang; Xu, Ting; He, Jia; Hong, Huarong; Jiang, Luyun; Peng, Shunlin; Xiong, Peizheng (Frontiers in Pharmacology, 2025)
BackgroundNasal drug delivery offers a non-invasive route with rapid absorption and the ability to bypass first-pass metabolism, making it promising for central nervous system (CNS) disorders, nasal diseases such as allergic rhinitis, and other chronic conditions by enabling targeted delivery and crossing the blood-brain barrier.PurposeTo review the advantages of nasal delivery, therapeutic potential of natural products, and how drug delivery systems may overcome bioavailability and solubility issues.Study DesignA literature review analyzing mechanisms, clinical applications, and limitations of natural products in nasal delivery.MethodsRelevant articles published before January 2025 were retrieved from Google Scholar, PubMed, ScienceDirect, Scopus, Web of Science, Springer, and official sources.ResultsNasal administration improves the bioavailability and absorption of natural products, enhancing anti-inflammatory, antioxidant, neuroprotective, and anti-allergic effects. However, poor solubility and stability remain barriers, which may be mitigated by nanocarriers, liposomes, and other advanced systems.ConclusionCombining nasal drug delivery with natural products is a promising strategy for treating CNS, nasal, and chronic diseases, potentially improving clinical efficacy and expanding therapeutic options.